Dampak Kebijakan Labelisasi Program Keluarga Harapan (PKH) Terhadap Penerima Manfaat Bantuan PKH di Kecamatan Tanjungpinang Timur - Siti Utari, Diah; Ambar Rinah, Sri; Nurliyanti Sigalingging, Dinda; Dwiniati, Dwiniati (Jurnal Ilmu Sosial dan Ilmu Politik, 2024)
The Family Hope Program (PKH) is a government program in providing social protection for poor families (KM). As part of poverty alleviation efforts through the provision of conditional assistance. However, the number of Family Hope Program (PKH) Beneficiary Families in East Tanjungpinang District was 2231, only 1976 houses were labeled, and the number of graduates increased. This study aims to determine the Impact of Family Hope Program (PKH) Labeling Policy on PKH Aid Beneficiaries in East Tanjungpinang District. This research method is qualitative descriptive. The data collection techniques used are observation, interviews, and documentation studies. The data is analyzed by qualitative techniques. Based on the results of research on the Impact of Family Hope Program (PKH) Labeling Policy on PKH Aid Beneficiaries in East Tanjungpinang District. The impact seen from the interview results and data findings is very clear with a decrease in the number of 300 PKH Beneficiary Family members resigning independently in Tanjungpinang City. In East Tanjungpinang District, there was a decrease of 176 PKH members. The impact felt by the government is in accordance with the objectives of the PKH labeling policy. The impact not only affects the policy itself but also affects PKH Beneficiary Family members.